Pengembangan Model Lengan sebagai Alat Peraga Alternatif Sederhana untuk Praktikum Imunisasi BCG - Erawati, Deasy; Wigunarti, Mirna; Pihahey, Priscilla Jessica (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT One of the midwifery services is providing complete basic immunization to babies, toddlers and pre-school children. In Indonesia, to prevent children from becoming infected with TB, the government has designated Bacille Calmette Guerin (BCG) immunization as mandatory immunization. When administering the BCG vaccine, it may occur that the BCG vaccine scar does not appear at the injection area. This can happen because the antibody level is too low, the dose is too low, the injection method is wrong, the child's immune system is decreasing) or the quality of the vaccine is not good due to the wrong storage method. To increase the knowledge and skills of midwives in providing BCG immunization, it is necessary to hold training/practicum on BCG immunization injections for students using appropriate learning media through laboratory practical activities. The aim of this research is to produce alternative teaching aids to support practical activities and to determine the feasibility of the BCG immunization injection teaching aids that have been made. This research used Research and Development (R&D) method. The research subjects were 38 respondents who were taken using purposive sampling techniques and consisted of students, lecturers and Clinical Instructor. The research was conducted at the D-III Midwifery Study Program, Manokwari, Health Polytechnic, Ministry of Health, Sorong, in May-October 2024. The teaching aids obtained were Simple Alternative Simulator for BCG Immunization developed by researchers which were equipped with a feature capable of displaying pale lumps on the surface of the skin follicles at the injection site as a sign that the injection was given correctly. The results is 25 respondents who took part in the field study, the total questionnaire score obtained was 3,396 with an ideal maximum total score of 3,750. The feasibility percentage obtained was 90.56%, so it can be concluded that the BCG immunization injection simulator is very suitable for use in the laboratory. Keywords: Intracutan, Simulator, Laboratory, BCG, Midwife  ABSTRAK Salah satu kompetensi pelayanan KIA oleh bidan adalah pemberian imunisasi dasar lengkap pada Bayi, balita dan anak pra sekolah. Di Indonesia untuk menghindari anak terinfeksi TB, pemerintah menetapkan imunisasi Bacille Calmette Guerin (BCG) sebagai imunisasi wajib. Pada pemberian vaksin BCG bisa terjadi scar vaksin BCG tidak muncul di daerah suntikan. Hal itu dapat terjadi karena kadar antibodinya terlalu rendah, dosis terlalu rendah, cara penyuntikkan yang salah, daya tahan anak sedang menurun) atau kualitas vaksinnya kurang baik akibat cara penyimpanan yang salah. Untuk meningkatkan pengetahuan dan keterampilan bidan dalam pemberian imunisasi BCG, maka perlu di adakan pelatihan/praktikum penyuntikan imunisasi BCG bagi mahasiswa dengan menggunakan media pembelajaran yang sesuai melalui kegiatan praktik laboratorium. Tujuan penelitian ini adalah menghasilkan alat peraga alternative sebagai penunjang kegiatan praktikum serta mengetahui kelaikan alat peraga peyuntikan imunisasi BCG yang telah dibuat. Penelitian ini merupakan Research and Develompment (R&D). Subjek penelitian berjumlah 38 responden yang diambil menggunakan teknik purposive sampling dan terdiri atas mahasiswa, dosen dan CI. Penelitian dilakukan di Prodi D-III Kebidanan Manokwari Poltekkes Kemenkes Sorong pada bulan Mei-Oktober 2024. Alat peraga yang diperoleh adalah Alat Peraga Alternatif Sederhana Untuk Praktikum Imunisasi BCG yang dikembangkan oleh peneliti yang dilengkapi dengan fitur mampu menampilkan benjolan pucat pada permukaan folikel kulit tempat suntikan sebagai tanda suntikan diberikan dengan benar. Dari 25 responden yang mengikuti studi lapangan, total skor kuesioner yang didapatkan sebesar 3.396 dengan total skor maksimal ideal 3.750. Prosentase kelayakan didapatkan hasil sebesar 90,56% sehingga dapat disimpulkan bahwa alat peraga penyuntikan imunisasi BCG yang dibuat Sangat Layak digunakan di laboratorium kebidanan untuk keperluan praktikum pemberian imunisasi BCG pada bayi. Kata Kunci: Intrakutan, Alat Peraga, Laboratorium, BCG, Bidan